2018
DOI: 10.1002/nafm.10175
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rearing Experience on the Survival, Growth, and Behavior of Hatchery‐Reared Largemouth Bass

Abstract: Largemouth Bass Micropterus salmoides are commonly stocked throughout their native range, but survival of stocked fish is variable and often low. Hatchery fish may have difficulty switching to natural forage; therefore, providing feeding experience with natural prey in the rearing environment could result in improved growth and survival of Largemouth Bass after stocking. We conducted pond experiments to evaluate differences in growth and survival of Largemouth Bass reared in raceways and fed pellets or in pond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Relative to stocked fry or hatchery fish reared on live forage, pellet‐reared hatchery fish often consume less prey (Bachman, 1984; Porak et al, 2002; Pouder et al, 2010; Reiriz et al, 1998; Sosiak et al, 1979), have lower prey capture efficiencies (Diana et al, 2018), consume fewer prey types (Diana et al, 2018; Sosiak et al, 1979) and are slower to switch to novel prey (Ersbak & Haase, 1983). The success of walleye stocking programmes is dependent on walleye recognising and successfully foraging on high caloric prey items that promote growth and improve condition and overwinter energy reserves.…”
Section: Discussionmentioning
confidence: 99%
“…Relative to stocked fry or hatchery fish reared on live forage, pellet‐reared hatchery fish often consume less prey (Bachman, 1984; Porak et al, 2002; Pouder et al, 2010; Reiriz et al, 1998; Sosiak et al, 1979), have lower prey capture efficiencies (Diana et al, 2018), consume fewer prey types (Diana et al, 2018; Sosiak et al, 1979) and are slower to switch to novel prey (Ersbak & Haase, 1983). The success of walleye stocking programmes is dependent on walleye recognising and successfully foraging on high caloric prey items that promote growth and improve condition and overwinter energy reserves.…”
Section: Discussionmentioning
confidence: 99%
“…Walleye (Sander vitreus) trained with live prey and stocked into small predator-free ponds showed no signifficant differences in survival and growth after either 15 or 30 d compared to naïve walleye, possibly reflecting the rapid learning of foraging skills indicated in lab trials (within 5 trial days; . In a similar pond-stocking experiment, prey-experienced largemouth bass (Micropterus salmoides) were found to grow faster than prey-naïve conspecifics, but survival did not differ between these groups (Diana et al 2018). Costas et al (2013) found no survival benefit of feeding Atlantic salmon juveniles with invertebrates for 2 wks prerelease in a 3-wk release experiment in a screened-off river section.…”
Section: Social Transfermentioning
confidence: 94%
“…Age-0 bass that are large enough to convert to piscivory generally exhibit increased growth compared to those that are not [8]. Moreover, pellet-reared largemouth bass may have difficulty recruiting within lakes compared to bass that are acclimated to capturing live prey fish [9]. Pellet-reared juvenile muskellunge (Esox masquinongy) showed lower post-stocking survival than minnow-reared fish, due to higher predation mortality [10].…”
Section: Introductionmentioning
confidence: 99%